Dead dogs don’t bite? Change and continuity in Peruvian recall referendums - Alva-Mendoza, Jair (Revista Elecciones, 2025)
In this study, I aim to describe the main changes and continuities in the dynamics of recall referendums towards Peruvian mayors as well as local councilors, known as consultas populares de revocatoria (CPR). I argue that although the frequency of referendums has dropped dramatically since the last legislative reform in 2015, the dynamics that explain their initiation, activation, and outcomes have not changed significantly. I arrive at this conclusion by analyzing the influence of three established determinants of CPRs— municipal budget, budget execution, and political competition—across the three stages of the recall process. This article makes a twofold contribution. First, it offers an updated and characterization of referendum through 2025. Second, these new patterns suggest that the recent legislative reform has rendered the instrumentalization of recalls as a ‘political weapon’ more difficult, it has also constrained a key mechanism of citizen accountability at a municipal level.